Reflections of associations and foundations’ applications in new media to increase the quality in disabled people’s lives - Ayman, Umut; Kaya, Anıl Kemal; Kağan, Sertan (Springer Netherlands rbk@louisiana.edu, 2018)
Associations and foundations (that support these associations) play a vital role in increasing the life quality of the society in general, and the disabled people in particular. Civil society organizations which place a significant emphasis on the society’s well-being play an active role both in the promotion of disabled people’s rights and the provision of equal opportunities for their active participation in social life. Disabled people represent a disadvantaged group in the society because they experience disadvantages in economic and social life. This study focuses on new media usage of nonprofit oriented associations that are established to support disabled people in Northern Cyprus as a developing country. The content analysis as a quantitative research methodology is used to analyze the Disabled Associations’ and some foundations’ web sites and their official Facebook pages to interpret their identities, their way of communication and their social responsibility projects for increasing the quality of life of disabled people and raising public awareness on disabled people’s rights. © 2018, Springer Science+Business Media B.V., part of Springer Nature.
Keywords: Disabled associations; New media; Northern Cyprus; Social responsibility projects